2023
DOI: 10.1186/s40001-022-00922-6
|View full text |Cite
|
Sign up to set email alerts
|

How to diagnose iron deficiency in chronic disease: A review of current methods and potential marker for the outcome

Abstract: Iron deficiency (ID) is the most common nutritional disorder worldwide. It is often observed in patients with chronic diseases, such as heart failure (HF), chronic kidney disease (CKD), inflammatory bowel disease (IBD) and cancer. ID is associated with poor clinical outcome, including poor performance, reduced quality of life, as well as increased hospitalization and mortality. The aim of this review is to provide an overview about the role of ID in chronic diseases (HF, CKD, IBD, cancer) regarding their curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 89 publications
0
14
0
Order By: Relevance
“…Previous guidelines have recommended the measurement of SF concentrations, and some proposed TSAT as an alternative or complementary to define ID, that is SF less than 100 g/mL or 100 to 299 ng/mL with TSAT less than 20% [ 3 ]. However, some recent studies have realized that TSAT is a reliable diagnostic maker for ID with high sensitivity and specificity and should be recommended in clinical practice and a novel definition of ID based on TSAT alone has been suggested [ 37 ]. In a pulmonary vascular disease study, researchers found that ID, defined by TSAT less than 21%, best identifies patients with worse functional status and adverse clinical outcomes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous guidelines have recommended the measurement of SF concentrations, and some proposed TSAT as an alternative or complementary to define ID, that is SF less than 100 g/mL or 100 to 299 ng/mL with TSAT less than 20% [ 3 ]. However, some recent studies have realized that TSAT is a reliable diagnostic maker for ID with high sensitivity and specificity and should be recommended in clinical practice and a novel definition of ID based on TSAT alone has been suggested [ 37 ]. In a pulmonary vascular disease study, researchers found that ID, defined by TSAT less than 21%, best identifies patients with worse functional status and adverse clinical outcomes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, individuals with DM had lower levels of TSAT compared to those without DM, and the Q1 group of TSAT was associated with higher CVD mortality risk and lower cancer mortality risk. TSAT reflects the proportion of circulating iron in the context of iron requirements and is less affected by inflammatory processes [ 37 , 39 , 40 ], which means the ID was more pronounced in individuals with diabetes leading to cardiomyocyte energy metabolism disorders, and increased risk of CVD mortality. In addition to its role in the generation of ROS, iron may be a limiting nutrient to the growth and replication of cancer cells in the human body, which may be responsible for the lowest cancer mortality risk when iron is deficient [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested iron deficiency could exist even with expected Hg results [ 73 ]. In such cases, low transferrin saturation and low ferritin levels could support a diagnosis of iron deficiency, especially if patients suffer from a chronic condition [ 73 , 74 , 75 ]. Iron is used by bacteria such as M. tuberculosis for growth and can even trigger HIV reactivation [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Absolute ID can occur in cases of increased demand, decreased iron intake or absorption, or chronic blood loss ( Table 1 ). Absolute ID is characterized by low levels of stored iron, resulting in low serum ferritin and reduced transferrin levels [ 7 ].…”
Section: Id Etiology and Classificationmentioning
confidence: 99%